The manufacture of microencapsulated phase change materials suitable for the design of thermally enhanced fabrics - Önder, Emel; SARIER, NİHAL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2007)
Thermal comfort of a fabric is one of the important tasks of the designers that require an engineering approach. In this study, we first aimed to establish a manufacturing technique based on in situ polymerization in order to accomplish the microencapsulation of phase change materials (PCMs) that can ultimately be used in different textile applications, i.e. incorporating such products into the multi-component non-conventional fabrics. This method is suitable for the laboratory-scale work as well as the industrial-scale one, considering some important issues like energy and time savings. Four types of polyurea-formaldehyde microcapsules containing different waxes and a control group of 100% shell material were produced and then examined by DSC, particle size and SEM analyses. Furthermore, we also focused on the contributions of microencapsulated PCMs to the thermal performances of fabrics of certain passive insulation characteristics for the given cold weather and physical activity conditions, based on the model developed for a multi-layer fabric system. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: microencapsulation; phase change materials; functional textiles; thermal; comfort; DSC; energy storage; microcapsules; mikrokapsülleme; faz değişim materyalleri; fonksiyonel tekstil; termal; konfor; enerji depolama; mikrokapsüller